An Evaluation of A Suggested Instructional Writing Model in Freshmen English Writing Classes in Iran - Naghdipour, Bakhtiar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
The curriculum for teaching undergraduate university students in Iran majoring in English generally includes paragraph writing during the third semester and essay writing (4-5 paragraphs) during the fifth semester. In spite of their titles, the firstyear ‘Grammar & Writing (I & II)’ courses offered in the first and second semesters cover grammar only and rarely go beyond sentence-level writing in support of the newly taught grammar. This policy has created a gap between writing and other language skills, making it difficult for these students to deal with the demanding writing tasks such as extended writing assignments and projects later in their academic or professional life. In addition, the syllabus for writing courses, offered during the second and third years, is product-based, which has deprived students of the opportunities to engage in meaningful writing activities and to receive effective and efficient feedback on their work. The current study, however, challenges the delay in teaching writing as well as the use of traditional approaches in writing classes, describing and evaluating a teaching intervention within the process genre approach in freshmen English translation writing classes. Both quantitative and qualitative data collection instruments including pre- and posttests, pre- and post-intervention questionnaires, timed writing tasks, semi-structured interviews, and observation notes were employed during different phases of the study to gain insights into students’ engagement with this instruction, and to triangulate the data collected from different sources. The instruction for each semester (16 weeks) was designed based on a three-session (modeling, composing, and feedback) modular instructional model that focused on helping students write within four rhetorical modes: descriptive, narrative, process, and cause and effect. The analysis of data from different sources revealed that students made a significant development in the fluency, accuracy, and quality of their writing over the course of the study. The results also indicated a significant change in students’ attitudes towards writing as well as their acquisition and use of effective writing strategies at both paragraph and essay levels. In particular, students perceived feedback, the incorporation of samples and authentic reading materials, and portfolio writing as the most successful elements of this instructional writing model. The findings of this study highlighted the effectiveness of a writing intervention in first-year writing classes, and suggested that postponing writing instruction per se until the second year is questionable and that applying an eclectic approach to writing pedagogy may better compensate for students’ needs and contextual deficiencies. In addition, the findings imply that the use of more post-product writing approaches can promote the integration of reading and writing skills and therefore support learning other language learning areas such as vocabulary, grammar, and reading. These findings could inform similar EFL contexts with respect to the consideration of a writing curriculum and pedagogy commensurate with students’ real needs in academic writing. Keywords: instructional writing model, process genre approach, curriculum design, writing pedagogy, writing assessment, feedback, portfolio writing, EFL, Iran

ÖZ: İran'da İngiliz dili eğitimi gören lisans öğrencilerinin yazma dersi öğretim programı genellikle üçüncü dönemde ‘paragraf düzeyinde yazma’yı, beşinci dönemde de (4-5 paragraflık) ‘kompozisyon yazma’yı içermektedir. Bu öğrencilere birinci ve ikinci dönemlerde 'Yazma ve Dilbilgisi' dersleri verilmesine karşın, bu dersler yalnızca dilbilgisi konularını içermekte ve daha çok yeni öğretilen dilbilgisi konularını destekleyen ve ender olarak cümle düzeyini aşan yazma alıştırmalarından oluşmaktadır. Bu durum yazma becerisi ile diğer dil becerileri arasında bir boşluk yaratmakta; bu da öğrencilerin daha sonraki akademik veya mesleki yaşamlarında başa çıkmak zorunda kalacakları uzun yazma ödevlerini ve projeleri, onlar için daha da zor hale getirmektedir. Buna ek olarak, ikinci ve üçüncü sınıfta verilen yazma derslerinin izlencesi ürün-odaklı olup, öğrencileri anlamlı yazma aktivitelerinden mahrum kılmakta, yazdıkları hakkında etkili ve yararlı geribildirim almalarına imkan tanımamaktadır. Bu çalışma ise, gecikmeli olarak yapılan yazma öğretimine ve yazma derslerinde geleneksel yaklaşımların takip edilmesine karşı çıkmakta olup, birinci sınıfta verilen yazma derslerinde süreç-tür tabanlı yaklaşım çerçevesinde devreye sokulan yeni bir öğretim tekniğinin yazma eğitimi ve izlencesinin geliştirilmesi açısından tanıtımını ve değerlendirilmesini amaçlamaktadır. Çalışmanın farklı evrelerinde, öğrencilerin bu yeni öğretim tekniğini nasıl karşıladıklarına ilişkin görüşlerini elde etmek amacıyla, uygulama öncesi ve sonrasında uygulanan anketler, sınavlar, yarı-resmi mülakatlar ve gözlem notları gibi hem niteliksel hem de niceliksel veri toplama araçları kullanılmış ve çeşitli kaynaklardan elde edilen veriler çeşitleme yöntemiyle karşılaştırılmıştır. 16 haftalık vi öğretim materyali, ‘modelleme’, ‘yazma’ ve ‘dönüt’ten oluşan üç oturumlu birimsel bir modeldir. Bu model öğrencilerin betimsel, anlatısal, süreç ve neden-sonuç biçimlerinde olmak üzere dört yazma biçiminde yazmaya odaklanmasına yardımcı olmuştur. Toplanan verilerin çözümlenmesi öğrencilerin yazma becerilerinin doğruluk, akıcılık ve kalite açısından anlamlı olarak geliştiğini ortaya çıkarmıştır. Sonuçlar, hem paragraf hem de kompozisyon yazma düzeyinde öğrencilerin yazma stratejileri edinmelerinin ve etkili biçimde kullanmalarının olumlu yönde değiştiğini göstermiştir. Öğrenciler, yazma öğretiminde kullanılan bu modelin en etkili öğeleri olarak, geribildirimi, örnek ve özgün materyallerin kullanılmasını ve yazma dosyası tutmayı saymışlardır. Araştırmada elde edilen bulgular yazma öğretimini ikinci sınıfa ertelemenin tartışılır olduğunu; birinci sınıftaki yazma derslerinde uygulanan yeni yazma öğretimi modelinin ise etkili olduğunu ortaya koymuştur. İzlenecek karma yaklaşımın, öğrencilerin yazma becerisine ilişkin gereksinimlerini karşılamada ve ortama dayalı eksikliklerin telafi edilmesinde etkili olabileceği görüşü de ortaya çıkan sonuçlar arasındadır. Bulgular ayrıca yazma öğretiminde güncel yöntemlerin kullanılmasının, öğrencilerin okuma ve yazma etkinliklerini bütünleştirmelerine yardımcı olduğunu; aynı zamanda sözcük, dilbilgisi ve okuma alanlarını desteklediğini de ortaya koymaktadır. Bu çalışma İngilizce’nin öğretimiyle uğraşan benzer kurumlarda öğrencilerin akademik yazmaya yönelik gerçek gereksinimlerini karşılayacak şekilde bir yazma dersi izlencesi ve öğretim yönteminin geliştirilmesi konusunda yol gösterici olabilir. Anahtar Sözcükler: öğretici yazma modeli, süreç-tür tabanlı yaklaşım, izlence tasarımı, yazma öğretimi, yazma becerisinin değerlendirilmesi, geribildirim, yazma dosyası, yabancı dil olarak İngilizce, Iran
Doctor of Philosophy in English Language Teaching (ELT). Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2014. Supervisor: Prof. Dr. Ülker Vancı Osam.
Keywords: English Language Teaching (ELT); English Language - Study and Teaching; English language - Study and teaching - Curricula--Iran; Instructional writing model; process genre approach; curriculum design; writing pedagogy; writing assessment; feedback; portfolio writing; EFL; Iran